Fade away - Coben, Harlan, 1962- (New York : Dell Publishing, 2008)
Sports agent Myron Bolitar had once aimed for a career in the NBA, until an injury cost him his chance to go pro, but when the star player for the New Jersey Dragons disappears without a trace, Bolitar takes the undercover assignment of his dreams--a position on the team.
"A Myron Bolitar novel."
Keywords: Bolitar, Myron (Fictitious character) -- Fiction; Sports agents -- Fiction; Basketball players -- Crimes against -- Fiction; New Jersey -- Fiction; Mystery fiction